Distribuição dos desembolsos do BNDES no setor sucroenergético no Brasil - Costa, Vera Mariza Henriques de Miranda [UNESP]; Borges, Ana Cláudia Giannini (My University, 2012)
The organization and dynamics of the energetic-sugarcane sector in Brazil have suffered the impacts of the “deregulation” process that took place in the 1990s, since when it is no longer monitored by the State. In this scenario, the agribusiness enterprises, in order to survive, act over production, marketing and management of their activities, among others areas, demanding financial investments. The credit lines offered by BNDES (National Bank for Economic and Social Development) are one of the factors that enable the implementation of these actions. In this context, the aim of this study is to assess the connections between BNDES's outlays for the sugarcane sector in Brazil from 2001 to 2008, and the activities of this sector, according to the federation unity and the region in the country. The work is based on: i) literature review and ii) secondary selected data collection aimed at the composition of data series. The organization and analysis of data indicates that the largest amount of money is destined to the south-central region, specifically the state of São Paulo. This is the only state that receives almost all types of financings, an equivalent to 68% of the receptions in the period. The concentration of BNDES's outlays in the south-central region may be linked to the dominance of the sector in this region, either in terms of harvested area, amount of production, employment contracts or number of enterprises.

Na década de 1990 ocorre a desregulamentação, impactando a organização e a dinâmica do setor sucroenergético, não mais monitorado pelo Estado. Nesse cenário, as agroindústrias, objetivando a sobrevivência, realizam ações direcionadas à produção, comercialização e gestão, dentre outras, o que demanda delas investimentos. Um viabilizador, para a efetivação dessas ações, é encontrado nas linhas de financiamento disponibilizadas pelo BNDES (Banco Nacional de Desenvolvimento Econômico e Social). Nesse contexto, o objetivo geral deste trabalho é avaliar a relação entre os desembolsos do BNDES para o setor sucroenergético, no Brasil, no período de 2001 a 2008, associado às atividades desse setor, considerando unidades da federação e grandes regiões do país. A execução do trabalho se desenvolveu a partir de: i) revisão bibliográfica e ii) coleta de dados secundários selecionados, para construção de séries. A organização e a análise dos dados indicam que o maior volume vai para a região Centro-Sul, especificamente, para o estado de São Paulo. Este estado é o único que capta quase todos os tipos de desembolsos, o que totalizou 68% das captações no período. A concentração da captação dos desembolsos na região Centro-Sul pode estar atrelada à predominância do setor nessa região, em área colhida, quantidade produzida de cana de açúcar, vínculos empregatícios e número de agroindústrias.
Localization of BNDES financial investments on the sugarcane sector in Brazil
Keywords: Sugarcane sector; BNDES financial support; South-central region; Setor sucroenergético; Desembolsos do BNDES; Região Centro-Sul